Conocimientos, actitudes y prácticas sobre alimentación saludable en adolescentes de los colegios del cantón Gonzanamá - Yaguana Jiménez, Josselyn Stefania (2022)
Adolescence is a stage of multiple physical and psychological changes, so there are a number of risks, including food, both for the increase in nutritional needs, as well as changes in physical activity, moods, eating habits and toxic substances that adolescents use. The purpose of this study was to determine the level of knowledge about nutrition among adolescents in the schools of the canton of Gonzanamá, as well as to establish their attitudes towards healthy eating and to know the practices they develop in relation to it. A descriptive study was conducted with a quantitative approach, determining a sample of 264 students, in whom the questionnaire of knowledge, attitudes and practices on healthy eating was applied, obtaining after data analysis that most of them 45.1% have a regular knowledge about healthy eating, followed by 30.7% corresponding to students who have a high knowledge and finally 24.2% who have a low knowledge; It was also evident that most of the participants 98.9% have a favorable and positive attitude towards healthy eating in contrast to 1.1% who have an unfavorable attitude and corresponds to students from schools in the parishes of Gonzanamá and Changaimina; finally in relation to the daily practices of healthy eating that adolescents develop, 49.3% have adequate practices and 50.7% responded that they do not have healthy practices. It is concluded that most of the adolescents have a regular knowledge about healthy eating, a favorable attitude towards it and inadequate eating practices